A method for predicting tensile strength of carbon fiber epoxy resin based composite materials at high temperature
Through the combination of thermogravimetric analysis and thermal analysis module, a tensile strength prediction model of carbon fiber epoxy resin-based composite materials at high temperatures was established, which solved the problem that the prior art could not effectively predict the tensile strength of the material at high temperatures, and achieved accurate consideration and prediction of the pyrolysis and softening phenomena of the material.
Patent Information
- Application Number
- CN202411584767.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-11-07
AI Technical Summary
The existing methods cannot effectively predict the tensile strength of carbon fiber epoxy resin-based composite materials at high temperatures, especially the influence of resin matrix softening, thermal decomposition and carbon fiber softening on material strength during the heating process.
Thermogravimetric analysis is used to determine the pyrolysis process and kinetic parameters of the material, combined with ANSYS software for thermal analysis, calculate the tensile strength of the material under high temperature environment, and use a hyperbolic function to establish a material's tensile strength degradation model at high temperature.
The accurate prediction of the tensile strength of carbon fiber epoxy resin-based composite materials at high temperatures is achieved, and the pyrolysis and softening of the material at high temperatures is taken into account, providing a theoretical basis for structural design and strength prediction.
Smart Images

Figure CN119086306B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of detection methods, and specifically relates to a method for predicting the tensile strength of a carbon fiber epoxy resin-based composite material at high temperature. Background Art
[0002] Carbon fiber resinforced epoxy resinmatrix composites (CFRCs) are used to manufacture on-board high-pressure hydrogen storage cylinders due to their high strength and flexible operation. They can effectively increase hydrogen storage density and reduce weight. Since composite cylinders store hydrogen at a pressure of up to 70MPa and are flammable, they will undergo irreversible pyrolysis reactions at high temperatures. If a car catches fire due to an accident, the mechanical properties of CFRCs will be greatly degraded under high temperature conditions, further affecting the load-bearing capacity of the composite layer, causing the cylinder's load-bearing capacity to decrease, increasing the risk of cylinder failure. In addition, studies on the thermal response and heat transfer characteristics of high-pressure hydrogen cylinders have shown that at the thermocouple indication temperature (minimum 600°C) required by the fire test, the outermost layer of the composite material is loose due to decomposition and does not have the load-bearing capacity, and when the cylinder fails, the temperature of the internal composite layer will increase to about 400°C. Therefore, establishing a method that can effectively predict the tensile strength of CFRCs at high temperatures can provide guidance for predicting the fire resistance performance of gas cylinders, lay the foundation for proposing methods for optimizing and regulating the fire resistance performance of gas cylinders, and avoid catastrophic accidents of gas cylinders in fire environments.
[0003] The existing methods for calculating the tensile mechanical properties of CFRCs are mainly:
[0004] Reference 1 “GIBSON AG, WU YS, EVANS JT, et al. Laminate theory analysis of composites under load in fire[J]. Journal of Composite Materials, 2006, 40(7): 639-658.” discloses a method for characterizing the softening process of a polymer matrix by fitting experimental data with an antisymmetric characteristic function, such as a hyperbolic tanh function. However, this method does not consider the effect of thermal decomposition of the resin on the strength degradation of the composite material, and is therefore not suitable for strength prediction in high temperature environments.
[0005] Reference 2 "LI Y, LI W, TAO Y, et al. Theoretical model for the temperaturedependent longitudinal tensile strength of unidirectional fiber reinforced polymer composites[J]. Composites Part B: Engineering, 2019,161: 121-127" discloses a theoretical prediction model for the longitudinal tensile strength of unidirectional fiber composites at different temperatures. However, the temperature of the experimental data used to verify the model is lower than the melting temperature of the polymer matrix, and its applicability to other temperature ranges remains to be verified. In addition, the model involves many parameters of the fiber and the matrix, which makes it inconvenient to apply in practice.
[0006] Therefore, it is urgent to establish a method that can predict the tensile strength of unidirectional carbon fiber epoxy resin-based composites under high temperature (20℃~450℃) environment based on the thermal softening and decomposition of CFRCs matrix and the softening of carbon fiber. Summary of the invention
[0007] In view of the fact that existing prediction methods cannot take into account the influence of resin matrix softening, thermal decomposition and carbon fiber thermal softening on the tensile strength of CFRCs during the heating process, the present invention proposes a method for predicting the tensile strength of carbon fiber epoxy resin-based composite materials at high temperatures. The method is based on thermogravimetric analysis results, conforms to the actual situation of high-temperature pyrolysis of materials, and solves the problem of tensile strength prediction of unidirectional CFRCs under the combined action of high temperature and stress.
[0008] In order to solve the above technical problems, the present invention proposes a method for predicting the tensile strength of a carbon fiber epoxy resin-based composite material at high temperature, comprising the following steps:
[0009] (1) Based on the thermogravimetric analysis test of the material, the pyrolysis process of the material is determined by the thermal weight loss curve of the material at different heating rates;
[0010] (2) Based on the differential thermogravimetric curve of the material at different heating rates, the peak temperature is obtained and the temperature range of each decomposition stage is determined;
[0011] (3) Determine the thermal decomposition kinetic parameters of the material based on the non-isothermal differential thermogravimetric curve and mechanism function of the carbon fiber epoxy resin based composite material, wherein the kinetic parameters include activation energy and pre-exponential factor;
[0012] (4) Preparation of unidirectional carbon fiber epoxy resin-based composite laminates;
[0013] (5) using the ANSYS software thermal analysis module to calculate the heating time required for the unidirectional carbon fiber epoxy resin-based composite laminate to reach a stable thermal equilibrium state;
[0014] (6) Determine the maximum tensile load of carbon fiber epoxy resin composite materials at different temperature points in a high temperature environment;
[0015] (7) Calculate the tensile strength of the carbon fiber epoxy resin-based composite material according to standard GB / T 3354-2014 to obtain a test value;
[0016] (8) Based on the pyrolysis degradation law of the carbon fiber epoxy resin-based composite material obtained from steps (1) to (5), a hyperbolic function is used to determine the tensile strength degradation model of the material at high temperature; based on the test value calculated in step (7), a curve of the change of tensile strength of the carbon fiber epoxy resin-based composite material with temperature is obtained.
[0017] In some embodiments of the present invention, in step (1), determining the pyrolysis process of the material comprises the following steps:
[0018] A carbon fiber epoxy resin-based composite material sample was cut and dried, and then subjected to thermogravimetric analysis. During the thermogravimetric analysis, the temperature of the sample was increased from 30°C to 950°C in an air environment at heating rates of 5°C / min, 10°C / min, 20°C / min, and 30°C / min, respectively.
[0019] In some embodiments of the present invention, the drying temperature is 50-60°C, preferably 55°C.
[0020] In some embodiments of the present invention, the drying time is 20-28 hours, preferably 24 hours.
[0021] In some embodiments of the present invention, in step (3), the pyrolysis kinetic parameters of the material are determined by using the Arrhenius formula to describe the change of the material reaction rate constant with temperature, the reaction rate and the conversion rate function:
[0022] (1);
[0023] (2);
[0024] in: α is the conversion rate, %; A is the pre-exponential factor; E is the activation energy, kJ / mol; R is the ideal gas constant, 8.314 J / (mol·K); T is the absolute temperature, K; nis the reaction order; f ( α ) is the mechanism function in differential form; m 0. m t and m f are the initial mass, mass at any time and final mass of the sample, g;
[0025] The Kissinger-Akahira-Sunose method is used to calculate the activation energy, and its basic form is:
[0026] (3);
[0027] Where: Heating rate β is a constant, β= dT / dt; is the integral function of the conversion rate, ;
[0028] The temperature points corresponding to the peak values of the DTG curve from the thermogravimetric analysis test are used. T p To calculate the activation energy:
[0029] (4);
[0030] in: β i is the heating rate of the ith test, °C / min; T pi is the peak temperature of each stage expressed in absolute temperature, °C.
[0031] In some embodiments of the present invention, in step (4), the preparation of the unidirectional carbon fiber epoxy resin-based composite laminate comprises the following steps:
[0032] First, a single-layer composite prepreg is made of carbon fiber and epoxy resin matrix; then, a unidirectional composite prefabricated plate is prepared by a vacuum bag-autoclave method; an aluminum alloy reinforcement sheet is pasted on the end of the prepared unidirectional composite prefabricated plate; finally, the unidirectional composite prefabricated plate with the aluminum alloy reinforcement sheet is divided into several specimens, and the length, width and thickness of the specimens are 330 mm, 25 mm and 2 mm, respectively.
[0033] In some embodiments of the present invention, the carbon fiber is carbon fiber used to manufacture vehicle-mounted composite hydrogen storage cylinders. The carbon fiber used to manufacture vehicle-mounted composite hydrogen storage cylinders has the characteristics of high strength and high modulus and can meet the special requirements of hydrogen storage cylinders, for example, Toray's T700 carbon fiber.
[0034] In some embodiments of the present invention, the epoxy resin matrix is a thermosetting epoxy resin, for example, 0164 resin from Wuxi Resin Factory.
[0035] In some embodiments of the present invention, in step (6), determining the maximum tensile load of the carbon fiber epoxy resin-based composite material at different temperature points in a high temperature environment comprises the following steps:
[0036] The sample is heated to the required temperature, kept warm, and stretched using a tensile test device equipped with a high-temperature heating furnace. The crossbeam displacement control mode is used until the sample breaks at the loading speed. The load-displacement curves of the carbon fiber epoxy resin-based composite material at different temperature points are obtained through the tensile test.
[0037] In some embodiments of the present invention, the insulation time is 15-25 min, preferably 20 min.
[0038] In some embodiments of the present invention, the loading speed is 0.5-1.5 mm / min, preferably 1 mm / min.
[0039] In some embodiments of the present invention, in step (7), the tensile strength is calculated as follows:
[0040] (5);
[0041] in: σ t is the tensile strength, MPa; P max is the maximum load borne by the specimen before failure, N; w is the width of the specimen, mm; h is the sample thickness, mm.
[0042] In some embodiments of the present invention, in step (8), the tensile strength degradation model of the material at high temperature is:
[0043] (6);
[0044] in, P 1, P 2 and P 3 represents the tensile strength at room temperature, the tensile strength between the two transformation processes and the final tensile strength, MPa; k 1 and k 2 represents the relaxation width, obtained by fitting; T 1 and T 2 is the transition temperature, °C.
[0045] In some embodiments of the present invention, in step (8), the applicable temperature of the curve of the change of tensile strength of the carbon fiber epoxy resin based composite material with temperature is 20°C to 450°C.
[0046] Compared with the prior art, the above technical solution of the present invention has at least the following technical effects or advantages:
[0047] (1) The present invention provides a method for calculating the tensile strength of a carbon fiber epoxy resin-based composite material under high temperature conditions, determining the pyrolysis process of the material during the heating process, determining the peak temperature of each stage, determining the insulation time required for a carbon fiber epoxy resin-based composite unidirectional laminate to reach a thermal equilibrium state, determining the tensile strength of the carbon fiber epoxy resin-based composite material at different temperature points under high temperature conditions, and determining the variation law and prediction method of the tensile strength of the material during the pyrolysis process. The prediction method of the present invention can truly and effectively characterize the tensile performance degradation process of the carbon fiber epoxy resin-based composite material under high temperature, and macroscopically predict the high-temperature tensile strength of the carbon fiber epoxy resin-based composite material.
[0048] (2) The method for predicting the tensile strength of carbon fiber epoxy resin-based composite materials at high temperatures provided by the present invention takes into account the influence mechanism of thermal softening, thermal decomposition of the resin matrix and high-temperature softening of carbon fiber on the tensile strength of CFRCs, providing a theoretical basis for the structural design and strength prediction of carbon fiber epoxy resin-based composite materials. At the same time, based on experimental data, the present invention establishes a high-temperature tensile mechanical property degradation model for carbon fiber epoxy resin-based composite materials, which can predict the tensile strength of carbon fiber epoxy resin-based composite materials in the temperature range of 20℃ to 450℃ with high reliability. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 It is the thermal decomposition process of carbon fiber epoxy resin based composite materials in air;
[0050] Figure 2 is the DTG curve of carbon fiber epoxy resin based composite material at different heating rates (air);
[0051] Figure 3 It is the process of pyrolysis of carbon fiber epoxy resin composite material and (1 / T pi )Fitted curve graph (air);
[0052] Figure 4 is the load-displacement curve of CFRCs unidirectional laminate at 20℃~450℃;
[0053] Figure 5 It is the fitting curve of the variation of tensile strength of CFRCs unidirectional laminates with temperature. DETAILED DESCRIPTION
[0054] The present invention is described in detail below in conjunction with the embodiments, so as to facilitate the understanding of the present invention by those skilled in the art. It is necessary to point out here that the embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Non-essential improvements and adjustments made to the present invention by those skilled in the art according to the above invention content should still fall within the scope of protection of the present invention.
[0055] In the following embodiments, the environment is an air environment under standard atmospheric pressure; the carbon fiber is T700 carbon fiber produced by Toray Industries, Inc., and the epoxy resin is 0164 resin produced by Wuxi Resin Factory.
[0056] Example 1
[0057] A method for predicting the tensile strength of a carbon fiber epoxy resin-based composite material at high temperature comprises the following steps:
[0058] (1) Based on the thermogravimetric analysis test of the material, the thermal decomposition process of the material is determined by the thermal weight loss curve of the material at different heating rates.
[0059] A carbon fiber epoxy resin-based composite material sample was cut from the gas cylinder, and the crude sample was first crushed and then sieved into small particles of about 0.2 mm. The sample mass was 10 mg to 20 mg. The sample was dried at 55 ° C for 24 hours. During the thermogravimetric analysis, the sample was heated from 30 ° C to 950 ° C at a heating rate of 5 ° C / min, 10 ° C / min, 20 ° C / min and 30 ° C / min, respectively, to obtain the thermal decomposition process of the carbon fiber epoxy resin-based composite material in the air environment, such as Figure 1 As shown (heating rate 10℃ / min, sample mass 19.657mg). The DTG curve shows that the thermal decomposition of carbon fiber epoxy resin-based composite materials roughly went through three stages. The first stage (300℃ to 420℃) is mainly the oxidative decomposition of the resin, gradually forming a charred body; the second stage (430℃ to 600℃) is the oxidative decomposition process of the resin decomposing to form a charred body. The third stage (700℃ to 950℃) is the oxidative decomposition of carbon fiber.
[0060] (2) Based on the differential thermogravimetric curve of the material at different heating rates, the peak temperature is obtained and the temperature range of each decomposition stage is determined.
[0061] Thermal decomposition process of carbon fiber epoxy resin based composites at different heating rates, such as Figure 2 The thermal decomposition parameters are shown in Table 1.
[0062] Table 1: Thermal decomposition parameters of carbon fiber epoxy resin based composites in air
[0063]
[0064] (3) The material thermal decomposition kinetic parameters, including activation energy and pre-exponential factor, were determined based on the non-isothermal differential thermogravimetric curve and mechanism function of the carbon fiber epoxy resin based composite material.
[0065] The Arrhenius formula is used to describe the change of material reaction rate constant with temperature, reaction rate and conversion rate function:
[0066] (1);
[0067] (2);
[0068] in: α is the conversion rate, %; A is the pre-exponential factor; E is the activation energy, kJ / mol; R is the ideal gas constant, 8.314 J / (mol·K); T is the absolute temperature, K; n is the reaction order; f ( α ) is the mechanism function in differential form; m 0. m t and m f are the initial mass, mass at any time and final mass of the sample, g.
[0069] The Kissinger-Akahira-Sunose method is used to calculate the activation energy, and its basic form is:
[0070] (3);
[0071] Where: Heating rate β is a constant, β= dT / dt; is the integral function of the conversion rate, ;
[0072] This method allows the temperature points corresponding to each peak of the DTG curve to be determined from the thermogravimetric analysis test. T p To calculate the activation energy, it can be transformed into the formula:
[0073] (4);
[0074] in: β i is the heating rate of the ith test, °C / min; T piis the peak temperature of each stage expressed in absolute temperature, °C.
[0075] According to the KAS method, the peak temperature of the thermogravimetric curve is selected (see Table 1), Yes (1 / T pi ) to obtain the carbon fiber epoxy resin composite material during pyrolysis under air and (1 / T pi ) is a fitting curve, such as Figure 3 The calculated pyrolysis kinetic parameters of the composite material at different stages under air are shown in Table 2.
[0076] Table 2: Composite material pyrolysis kinetic parameters calculated by KAS method (air)
[0077]
[0078] The pyrolysis kinetics analysis of CFRCs further confirmed its three-step decomposition process and quantitatively gave the activation energy. In the first stage, epoxy resin is the main raw material for the decomposition reaction, and after decomposition, it will form a relatively stable charred product. In the second stage, under the action of oxygen, the charred product of the initial decomposition of epoxy resin can be further decomposed, and with the increase of temperature, the carbon fiber is also oxidized and decomposed in the third stage.
[0079] (4) Preparation of unidirectional carbon fiber epoxy resin based composite laminate specimens.
[0080] Firstly, a single-layer composite prepreg was made of carbon fiber T700 and thermosetting epoxy resin matrix 0164 used in manufacturing vehicle-mounted composite hydrogen storage cylinders. Then, a vacuum bag-autoclave method was used to prepare a unidirectional composite prefabricated plate. After that, an aluminum alloy reinforcement sheet was pasted on the end of the specimen to increase the friction force and avoid the slippage of the directly clamped specimen during the stretching process. Finally, the prefabricated plate with the reinforcement sheet was divided into several specimens, and the length, width and thickness of the specimens were 330 mm, 25 mm and 2 mm, respectively.
[0081] (5) The thermal analysis module of ANSYS software is used to calculate the heating time required for the composite laminate to reach a stable thermal equilibrium state.
[0082] The three-dimensional geometric model of CFRCs was established with reference to the unidirectional laminate specimens, and the boundary conditions of the three-dimensional heat conduction model were set according to the high-temperature furnace heating method of the MTS tensile testing machine used in the test. The heat conduction is mainly heat convection and heat conduction. The solid90 unit was selected to mesh the physical model, and the load was applied and analyzed and solved. It was calculated that it took about 18 minutes for the specimen to heat up to the highest test temperature of 450℃ and reach equilibrium, so the heating time was set to 20 minutes.
[0083] (6) Determine the maximum tensile load of carbon fiber epoxy resin based composites at different temperature points in a high temperature environment.
[0084] A tensile test device equipped with a high-temperature heating furnace was used to first heat the environmental chamber to the required temperature. Then, the stretching was started directly after keeping the temperature for 20 minutes. The crossbeam displacement control mode was used to continuously load the sample at a loading speed of 1 mm / min until the sample broke. The load-displacement curves of the carbon fiber epoxy resin-based composite material at different temperature points (the temperature gradually increased) were obtained through the tensile test. Figure 4 The load-displacement curves of CFRCs unidirectional laminates at 20℃~450℃ are shown. Figure 4 It can be seen that the fracture process of the sample can be roughly divided into three stages. The first stage is the elastic straight line segment, and the curve is relatively smooth. In the second stage, the curve begins to show "ripples (sawtooths)", but it is basically a linear relationship. Since the fiber modulus is higher than the matrix modulus, the stress-strain relationship in this section depends on the mechanical properties of the fiber. Small strands of fibers begin to break, and the load is affected. The surrounding resin matrix retransmits the fracture stress to other fibers, causing the fibers to bear an increased load and break one after another. The third stage is the fracture stage, and the curve suddenly drops, indicating that the sample breaks instantly. The sample suffers macroscopic damage due to the cumulative effects of matrix cracking, fiber pullout, interface debonding, and other damage.
[0085] (7) Calculate the tensile strength according to the formula provided in standard GB / T 3354-2014.
[0086] (5);
[0087] in: σ t is tensile strength, MPa; P max is the maximum load that the specimen can withstand before failure, N; w is the width of the specimen, mm; h is the sample thickness, mm.
[0088] The average values and dispersion coefficients of tensile strength of CFRCs unidirectional laminates at different temperatures are shown in Table 3.
[0089] Table 3: Tensile strength of unidirectional laminate specimens at different temperatures
[0090]
[0091] (8) Based on the pyrolysis degradation law of carbon fiber epoxy resin based composite materials obtained from steps (1) to (5), an improved hyperbolic function is used to determine the tensile strength degradation model of the material at high temperature.
[0092] Hyperbolic functions can be used to simulate a significant relaxation process of thermosetting resin matrix composites in a certain temperature range:
[0093] ;
[0094] in: P U and P R Represents the performance data at "non-relaxed" (low temperature) and "relaxed" temperature (high temperature), k represents the relaxation width, obtained by fitting, T 1 represents the "transition" temperature, which is the temperature at which the tensile properties drop to 50% of their initial value. The property-temperature curve described by this equation is generally antisymmetric on both sides of the transition temperature.
[0095] pass Figure 5 As can be seen from the above analysis, although the tensile strength of the composite material measured by the present invention does not show an obvious sudden drop trend near the glass transition temperature, it shows a continuous downward trend in the temperature range of 20℃~200℃ and the temperature range of 250℃~450℃, respectively. In the temperature range of 200℃~250℃, there is little change, and a small "platform" appears, dividing the entire mechanical property degradation process into two stages. Therefore, the present invention proposes to establish a degradation model in the form of hyperbolic functions that are characterized and added separately, on the premise that the effect of temperature on performance can be accumulated. According to the corresponding temperature of the change process, it is divided into two stages, the first stage is 20℃~250℃, and the second stage is 250℃~450℃. The improved hyperbolic function expression for characterizing the degradation law of the tensile properties of composite materials in the entire temperature range is as follows:
[0096] (6);
[0097] in: P 1, P 2 and P 3 represents the tensile strength at room temperature, the tensile strength between the two transformation processes and the final tensile strength, MPa; k 1 and k 2 represents the relaxation width, obtained by fitting; T 1 and T 2 is the transition temperature, °C.
[0098] Figure 5 The figure shows the degradation curve of the tensile strength of carbon fiber epoxy resin matrix composite material with temperature obtained by fitting the test value using formula (6). Table 4 shows the parameter values in formula (6).
[0099] Table 4: Parameter values in formula (6)
[0100]
[0101] from Figure 5 It can be seen that the curve fitting degree is relatively high. R 2 is 0.9854, which is consistent with the variation law of the tensile strength test value of the unidirectional laminate specimen between 20℃ and 450℃. For the first stage (20℃~250℃), since the amorphous polymer such as epoxy resin only undergoes glass transition before being heated to the decomposition temperature, the above hyperbolic function is used to characterize the degradation law of mechanical properties with temperature. For the second stage, due to the lack of tensile mechanical property test data involving the thermal decomposition temperature range, some studies have adopted a simple multiplication of the hyperbolic function by the power function factor R n However, according to the present invention, the degradation law of the tensile strength of carbon fiber epoxy resin-based composite materials in the second stage (250℃~450℃) is not suitable for power function characterization. Furthermore, according to the above analysis of the degradation mechanism of mechanical properties, at about 300℃, epoxy resin begins to decompose, the carbon fiber-resin interface is destroyed, stress cannot be effectively transmitted, and the tensile strength decreases significantly with increasing temperature. Since the effect of temperature on the degradation of tensile strength is a cumulative process, it is more appropriate to use the hyperbolic tangent function relationship to fit the degradation law of this stage.
[0102] Finally, the tensile strength prediction model of unidirectional carbon fiber epoxy resin-based composite materials under high temperature (20℃~450℃) environment is obtained as follows:
[0103] (7);
[0104] For ordinary technicians in the technical field to which the present invention belongs, they can make some simple deductions or substitutions without departing from the concept of the present invention, without having to go through creative work. Therefore, based on the disclosure of the present invention, simple improvements made by those skilled in the art to the present invention should be within the scope of protection of the present invention. The above embodiments are preferred embodiments of the present invention.
[0105] For example, all prediction methods similar to the present invention and equivalent changes made thereto should fall within the protection scope of the present invention.
Claims
1. A method for predicting the tensile strength of carbon fiber epoxy resin-based composite materials at high temperatures, characterized in that: The following steps are involved: (1) Based on the thermogravimetric analysis test of the material, the pyrolysis process of the material is determined by the thermal weight loss curve of the material at different heating rates; (2) Based on the differential thermogravimetric curve of the material at different heating rates, the peak temperature is obtained and the temperature range of each decomposition stage is determined; (3) Determine the thermal decomposition kinetic parameters of the material based on the non-isothermal differential thermogravimetric curve and mechanism function of the carbon fiber epoxy resin based composite material, wherein the kinetic parameters include activation energy and pre-exponential factor; The pyrolysis kinetic parameters of the material are determined by using the Arrhenius formula to describe the change of the material reaction rate constant with temperature, the reaction rate and the conversion rate function: (1); (2); in: α is the conversion rate, %; A is the pre-exponential factor; E is the activation energy, kJ / mol; R is the ideal gas constant, 8.314 J / (mol·K); T is the absolute temperature, K; n is the reaction order; f ( α ) is the mechanism function in differential form; m 0. m t and m f are the initial mass, mass at any time and final mass of the sample, respectively; g is the time; The Kissinger-Akahira-Sunose method is used to calculate the activation energy, and its basic form is: (3); Where: Heating rate β is a constant, β= dT / dt; is the integral function of the conversion rate, ; The temperature points corresponding to the peak values of the DTG curve from the thermogravimetric analysis test are used. T p To calculate the activation energy: (4); in: β i is the heating rate of the ith test, °C / min; T pi is the peak temperature of each stage expressed in absolute temperature, °C; (4) Preparation of unidirectional carbon fiber epoxy resin-based composite laminates; (5) using the ANSYS software thermal analysis module to calculate the heating time required for the unidirectional carbon fiber epoxy resin-based composite laminate to reach a stable thermal equilibrium state; (6) Determining the maximum tensile load of the carbon fiber epoxy resin-based composite material at different temperature points under a high temperature environment, comprising the following steps: using a tensile test device equipped with a high temperature heating furnace, heating the sample to a desired temperature, keeping the temperature, stretching, and using a crossbeam displacement control mode until the sample breaks at a loading speed; obtaining the load-displacement curve of the carbon fiber epoxy resin-based composite material at different temperature points through a tensile test; (7) Calculate the tensile strength of the carbon fiber epoxy resin-based composite material according to standard GB / T 3354-2014 to obtain a test value; (8) Based on the pyrolysis degradation law of the carbon fiber epoxy resin-based composite material obtained from step (1) to step (5), a hyperbolic function is used to determine the tensile strength degradation model of the material at high temperature; The tensile strength degradation model of the material at high temperature is: (6); in, P 1, P 2 and P 3 represents the tensile strength at room temperature, the tensile strength between the two transformation processes and the final tensile strength, MPa; k 1 and k 2 represents the relaxation width, obtained by fitting; T 1 and T 2 is the transition temperature, °C; Based on the test value fitting calculated in step (7), a curve of the change of tensile strength of the carbon fiber epoxy resin based composite material with temperature is obtained.
2. The method for predicting tensile strength of carbon fiber epoxy resin based composite materials at high temperature according to claim 1, characterized in that: In step (1), determining the pyrolysis process of the material comprises the following steps: A carbon fiber epoxy resin-based composite material sample was cut and dried, and then subjected to thermogravimetric analysis. During the thermogravimetric analysis, the temperature of the sample was increased from 30°C to 950°C in an air environment at heating rates of 5°C / min, 10°C / min, 20°C / min, and 30°C / min, respectively.
3. The method for predicting tensile strength of carbon fiber epoxy resin based composite materials at high temperature according to claim 2, characterized in that: The drying temperature is 50-60° C.; and / or the drying time is 20-28 hours.
4. The method for predicting tensile strength of carbon fiber epoxy resin based composite materials at high temperature according to claim 1, characterized in that: In step (4), the preparation of the unidirectional carbon fiber epoxy resin-based composite laminate comprises the following steps: First, a single-layer composite prepreg is made of carbon fiber and epoxy resin matrix; then, a unidirectional composite prefabricated plate is prepared by a vacuum bag-autoclave method; an aluminum alloy reinforcement sheet is pasted on the end of the prepared unidirectional composite prefabricated plate; finally, the unidirectional composite prefabricated plate with the aluminum alloy reinforcement sheet is divided into several specimens, and the length, width and thickness of the specimens are 330 mm, 25 mm and 2 mm, respectively.
5. The method for predicting tensile strength of carbon fiber epoxy resin based composite materials at high temperature according to claim 4, characterized in that: The carbon fiber is carbon fiber used to manufacture vehicle-mounted composite material hydrogen storage cylinders; and / or the epoxy resin matrix is a thermosetting epoxy resin.
6. The method for predicting tensile strength of carbon fiber epoxy resin based composite materials at high temperature according to claim 1, characterized in that: In step (7), the calculation formula of the tensile strength is: (5); in: σ t is the tensile strength, MPa; P max is the maximum load borne by the specimen before failure, N; w is the width of the specimen, mm; h is the sample thickness, mm.
7. The method for predicting tensile strength of carbon fiber epoxy resin based composite materials at high temperature according to claim 1, characterized in that: In step (8), the applicable temperature of the carbon fiber epoxy resin-based composite material tensile strength versus temperature curve is 20°C to 450°C.
Citation Information
Patent Citations
Method for predicting tensile strength of woven ceramic-based composite material
CN109781546A
Method for testing high-temperature mechanical properties of carbon fibers
CN112858034A
Cited By
Method for predicting residual tensile strength of CFRP after fire
CN122365905A